Functional materials for medical and biological purposes on the system CaO-CaF₂-P₂O₅-H₂O and additives - Krivileva, S.; Moiseev, V. (Functional Materials, 2018)
The system of CaO-P₂O₅ has been studied, he polymorphism of Ca₃(PO₄)₂ has been verified, he position of binary eutectics and the melting points in them on he Ca₃(PO₄)₂-Ca₄P₂O₉ segment have been determined. A diagram of the state of the CaO-P₂O5 system is constructed. The experimental verification of the calculated data by the high-temperature microscopy method in sity is performed. The regions of primary crystallization of phases in the system Ca₃(PO₄)₂-CaCO₃-Ca(OH)₂-H₂O are refined. The subsolidus structure of the systems CaO-CaF₂-P₂O₅-H₂O and CaO-CaF₂-P₂O₅-H₂O has been studied. The areas promising for the synthesis of materials based on CaO-CaF₂-P₂O₅-H₂O system and additives for the reconstruction of structural defects of the skeleton are established.